EFFORTS TO IMPROVE THE ABILITY OF BASIC PASSING TECHNIQUES UNDER THE GAME OF VOLLEYBALL THROUGH PAIRED METHODS - Yasriuddin Yasriuddin; Suwardi Suwardi; Muh Adnan Hudain; A Farhum Setiawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
This research is a classroom action research that aims to improve the ability of the basic technique of passing down in volleyball games through the pair method in Class X TKJ SMKN 5 Bone. This is due to students learning outcomes on the material passing under volleyball is still low while down passing is a technique the most basic and also the easiest for students to do. So that researchers want that in the implementation of learning there is an intensity of activity because students are able to practice these skills through learning activities with the pair method. The research was carried out in two cycles, each cycle consisting of planning, implementation, action, observation, and reflection. The research subjects were students of class X TKJ 1, totaling 36 students. There are 24 male students and 12 female students. Data collection techniques are by tests, observations, documentation, and field notes. Data analysis used quantitative descriptive statistical analysis techniques. The results showed that through the pair method can improve the ability of the basic technique of passing down in volleyball games in class X TKJ 1 SMKN 5 Bone. The results of the data obtained from the results of the first cycle of students who completed 41.67% with a frequency of 15 students, then increased in cycle II and students who completed 94.44% with a frequency of 34 students. The conclusion of this study is that through the pair method in learning passing down in volleyball games can improve student learning outcomes in class X TKJ SMKN 5 Bone.